Effect of CaO additive on the phase constitution and microstructure of fused BaZrO3 refractory. (27th June 2018) - Chen, Guangyao; Lan, Baobao; Xiong, Fuhao; Gao, Pengyue; Qin, Ziwei; Lu, Xionggang; Li, Chonghe
Abstract: The CaO doped fused BaZrO3 is a promising refractory for induction melting of titanium alloys. Therefore, the present study investigated the effect of CaO additive on the phase constitution and microstructure of the fused BaZrO3 refractory by x-ray diffraction (XRD) and scanning electron microscopy (SEM). Results revealed that the fused BaZrO3 refractory contained a significant amount of ZrO2 as a second phase. After doping CaO, the ZrO2 phase was absent along with the formation of phase-1 (Ba1− x Ca x ZrO3− σ ) and phase-2 (Ba1− y Ca y ZrO3− σ ) due to the different replacement ratio of Ca for Ba-site. The fraction of phase-1 was increasing as well as the decreasing fraction of phase-2 with the increased content of CaO additive. Meanwhile, CaO functions as a role of sintering additive for improving the densification of fused BaZrO3 refractory due to the generation of solid solutions. The result of interaction analysis indicated that CaO should be a suitable additive for improving the thermodynamic stability of fused BaZrO3 refractory. It provides an effective framework for the further development of CaO doped fused BaZrO3 refractory for induction melting of alloys rich in titanium.